2005
DOI: 10.1002/bem.20141
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural effects of electromagnetic fields

Abstract: Very few laboratory studies in children have explored the effects of exposure to low level electromagnetic fields (EMFs) on neurobehavioural function. Studies investigating effect on neurotransmitters, cognitive function and brain activity in adults and animals indicate that acute exposure to EMFs does not appear to engender any consistent physiological or behavioural impairment although a few subtle effects may occur. This suggests that exposure of children to low level EMFs may not cause significant detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 115 publications
(81 reference statements)
0
33
0
2
Order By: Relevance
“…29 Neurobehavioral studies in volunteers and in animals, mostly in adults, have not reported robust responses to ELF exposure 31 ; overall, any changes seen have been subtle, transient, and reversible. Workshop participants thought that there is no reason to suppose a greater sensitivity of CNS neural networks and ion channels to induced electric fields in children or in the embryo or fetus.…”
Section: Health Risks To Children From Elf Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Neurobehavioral studies in volunteers and in animals, mostly in adults, have not reported robust responses to ELF exposure 31 ; overall, any changes seen have been subtle, transient, and reversible. Workshop participants thought that there is no reason to suppose a greater sensitivity of CNS neural networks and ion channels to induced electric fields in children or in the embryo or fetus.…”
Section: Health Risks To Children From Elf Fieldsmentioning
confidence: 99%
“…Neurobehavioral studies in volunteers and in animals, mostly adults, have not reported robust responses to RF exposure, particularly that associated with mobile phones. 31 Numerous studies have evaluated developmental effects of RF fields on mammals, birds, and other nonmammalian species. 53,54 These studies have shown clearly that RF fields are teratogenic at exposure levels that are high enough to cause significant increases in temperature.…”
Section: Health Risks To Children From Rf Fieldsmentioning
confidence: 99%
“…Wpływ PEM na procesy poznawcze Mimo niezwykle obiecujących wyników badań z 2000 r. [12,13] do ok. 2005 r. stwierdzano głównie niewielki przemijający wpływ oddziaływania PEM na procesy pamięciowe i poznawcze [70,71]. W pracach późniejszych, w miarę poprawiania się metodyki badań dotyczących tego problemu, coraz częściej nie stwierdzano żad-nych efektów oddziaływania PEM telefonii komórko-wej na procesy poznawcze.…”
Section: Wpływ Pem Na Układ Krążenia I Jego Regulacjęunclassified
“…Elektromanyetik alanların (EMA) çok sayıda biyolojik fonksiyonları hücresel, davranışsal ve nörobiyolojik dü-zeyde etkilediği bilinmesine rağmen etki mekanizmaları tam olarak aydınlatılmış değildir (1,2). Genel olarak, EMA ile ilgili parametrelerin değişkenliği ve gerçek biyolojik etkileri ilgili bilgilerin sınırlı olması nedeniyle aktiviteleri ile ilgili değerlendirme yapmak oldukça güçtür.…”
Section: Introductionunclassified